2021
DOI: 10.1038/s41531-021-00173-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards optimising experimental quantification of persistent pain in Parkinson’s disease using psychophysical testing

Abstract: People with Parkinson’s disease (PD) may live for multiple decades after diagnosis. Ensuring that effective healthcare provision is received across the range of symptoms experienced is vital to the individual’s wellbeing and quality of life. As well as the hallmark motor symptoms, PD patients may also suffer from non-motor symptoms including persistent pain. This type of pain (lasting more than 3 months) is inconsistently described and poorly understood, resulting in limited treatment options. Evidence-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 112 publications
1
7
0
Order By: Relevance
“…On that, sensory profiling PwP through psychophysical testing can provide insight of the underlying mechanisms of persistent pain, thus providing a ‘refinement tool’ in terms of prescribed treatment strategies. However, amongst others, clinical heterogeneity of the pain type(s) presented adds a layer of complexity to this process [29]. Catechol-O-methyltransferase inhibitors (COMTi) may also be used as an add-on to levodopa when there is a need to optimize DRT, and opicapone, a third-generation COMTi, is currently being investigated for dopaminergic pain relief in PD (OpiCapone Effect on motor fluctuations and pAiN - OCEAN study, EudraCT Number 2020-001175-32).…”
Section: Dopaminementioning
confidence: 99%
See 1 more Smart Citation
“…On that, sensory profiling PwP through psychophysical testing can provide insight of the underlying mechanisms of persistent pain, thus providing a ‘refinement tool’ in terms of prescribed treatment strategies. However, amongst others, clinical heterogeneity of the pain type(s) presented adds a layer of complexity to this process [29]. Catechol-O-methyltransferase inhibitors (COMTi) may also be used as an add-on to levodopa when there is a need to optimize DRT, and opicapone, a third-generation COMTi, is currently being investigated for dopaminergic pain relief in PD (OpiCapone Effect on motor fluctuations and pAiN - OCEAN study, EudraCT Number 2020-001175-32).…”
Section: Dopaminementioning
confidence: 99%
“…Interestingly, although quantitative sensory testing (QST) revealed decreased heat-and cold pain thresholds in PwP following long-term MC use, in a single-arm, open-label studies PD patients reported significantly lower pain scores on the VAS after smoking MC, particularly for central PD-related pain [59,60]. Moving forward, the experimental assessment of pain in PwP upon application of paradigms including QST will be improved as a consensus regarding the methodological approach and precise experimental paradigm employed is reached [29].…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Pain intensity is subjective and best described through self-report, which is both accurate and reliable, even in the cognitively impaired [11][12][13][14]. Various pain scales have been utilized in PD studies, but many of these tools are not suitable for use in routine clinical care due to their time requirements [15]. Thus, an efficient pain screening strategy might encompass profiling pain using generic health-related quality of life (HRQoL) tools that have shown construct validity in PWP [16].…”
Section: Introductionmentioning
confidence: 99%
“… 36 37 Additionally, apathy and anxiety can increase the risk of motor complications (motor fluctuations and motor disorders), 38 which may affect patients' early exercise compliance. Pain affects up to 85% of PwPDs, but because of lack of treatment strategies to improve the analgesic effect, 39 50% of patients do not receive treatment or receive inadequate treatment. 40 In addition, 98% of PwPDs have been reported to experience nocturnal sleep disorders; 41 excessive daytime sleep and fatigue have shown different negative effects on home exercise.…”
Section: Discussionmentioning
confidence: 99%